Psychological well being and self care practices of patient with hypertension / Siti Khuzaimah Ahmad Sharoni, Nurul Syakila Naziron, Nurul Ashikin Hamzah, and Siti Rohaida Mohamed - Naziron, Nurul Syakila; Hamzah, Nurul Ashikin (Faculty of Business Management, 2013)
This study identified the types of self-care practices that hypertensive patient in Malaysia adhered most, determined their psychological and social well being and examined the association between self-care practices and psychological. This study used cross-sectional and was conducted in Kuala Lumpur Hospital (HKL) between September 2012 to June 2013, engaging 193 respondents. Most hypertensive showed the symptoms of depression, 63.21% (n=122) but were having moderately high social support with total mean scores of emotional support, tangible support, affectionate support, and positive social interaction were 3.73, 3.98, 3.96 and 3.54 respectively. There was no significant relationship between psychological with adherence to physical activity and weight management, p=0.359 and p=0.358. However, the presence of depression was affecting the medication adherence and adherence to low salt diet with p=0.042 and p=0.001 respectively.